THE INTERNATIONAL FOOD AID ON CIVIL WARS: HUMANITARIAN RELIEF OR SCOURGE INTENSIFYING? - Lima, Thiago (2024)
This article aims to understand the effects of foreign food aid on civil wars, a theme so far incipientin International Relations field in Brazil. The analysis identified that the aid may influence five aspects of civil wars: deflagration, risk, duration, indirect effects and deaths from strengthening of warring groups. Although there is no consensus on how these aspects are affected, it is argued that knowing and debating them is a fundamental step to improve the planning of humanitarian aid.